Políticas de formação da rede municipal de educação de Rondonópolis - MT (2004 a 2008) e suas contribuições para a formação continuada na escola : dos cursos propostos à visão da coordenação pedagógica - Mingareli, Regina Celia Farias (2011)
This paper is part of the Master‟s in Education Program at PPGE/UFMT and aims to understand whether the public policies on teachers‟ continuous education by the Municipal Secretariat of Education in Rondonópolis, State of Mato Grosso, Brazil, from 2004 to 2008, collaborate/d with the continuous education that has taken place inside the school. It is a qualitative research based on interviews as a source of data collection, along with document analysis. The study analysis focused on three topics: continuous education offered by SEMEC from 2004 to 2008; continuous education in the school and the school coordinators‟/supervisors‟ conceptions of training, being the subjects of the study. Its main theoretical-methodological references are found in Candau (2001), Carvalho (2005), Freire (1996, 1997, 2005), Geraldi (1999), Imbernón (2006, 2009), Marin (1995, 2003), Nóvoa (1991, 1992, 1995, 1997, 2009), Bogdan and Bilklen (1994), Ludke and André (1986), among others. From the research based on documents in the Department of Administration and School Registration, when data on the courses carried out during the previously mentioned period were collected, it was evident that the municipality has offered courses for different graduations, in several models, and has promoted continuous education as courses, seminaries and congresses, in a discontinued way, having sporadic, intensive and fast adoption, with reduced teaching/studying hours and taken as a training which does not cover the teachers‟ needs, since they do not start from their own reflection, challenges and everyday practice. The interviews with the supervisors/coordinators, who are some of the people in charge for the organization and adoption of the continuous education carried out in these schools, reveal it is necessary that the Secretariat subsidize the teachers‟ continuous education, mostly inside the school area, based on the comprehension that the teachers‟ working environment is a privileged locus for the building-up process of his/her autonomy and emancipation. Although, according to the interviewees, the school as a working group does not give the educational process carried out in the school its credit as a true space for continuous education, there is the understanding from their side that such actions are supposed to stimulate the study among peers, followed by discussions based on reflections about their practice and with theoretical background that allows the teacher to think and to change his/her performance in the classroom. Also comes out of their testimonies the very fact that the school and the Secretariat need to invest in a consistent program, in order to contribute to the educator‟s professional emancipation. It is also clear the importance of articulation between theory and practice in the performance of a praxis that is intended to be emancipatory and conscious of the possibilities and limits that the educational activity presents.